2012
DOI: 10.1111/j.1532-950x.2012.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Dynamics Analysis Evaluation of Tibial Tuberosity Advancement for Cranial Cruciate Ligament Failure in Dogs

Abstract: Affected limbs had a reduction in power of the stifle flexors. Irrespective of the side of CCLF, TSM was larger on the right side and the stifle extensor moment in late stance was larger on the left, perhaps indicating a mechanical limb dominance effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, kinematic analyses of the TPLO showed no significant differences between hind legs treated with TPLO and the contralateral sound leg within the mid-term follow-up (7) and normal or near normal values of sound dogs were measured at long-term follow-ups (33,49). In contrast, kinematic analyses that compared stifle power during early stance in the affected TTA treated and the sound leg, still measured reduced values on the affected side after 1 year, indicating a mechanical function deficit (11).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, kinematic analyses of the TPLO showed no significant differences between hind legs treated with TPLO and the contralateral sound leg within the mid-term follow-up (7) and normal or near normal values of sound dogs were measured at long-term follow-ups (33,49). In contrast, kinematic analyses that compared stifle power during early stance in the affected TTA treated and the sound leg, still measured reduced values on the affected side after 1 year, indicating a mechanical function deficit (11).…”
Section: Discussionmentioning
confidence: 87%
“…No considerable differences in outcome parameters (as determined by the owners) were found between the TPLO and TTA treatments. Owner satisfaction was, in general, high (4,9,11,24,30,31,35,58,69,70), and owners reported their dogs being free from lameness or having only mild residual lameness (9,11,18,24,31,35,37,50,59,65,71,74). For both techniques, studies had reported one third to two thirds of the patients suffering from long-term postoperative pain, to an uncertain degree (34,37,65).…”
Section: Owner Surveysmentioning
confidence: 99%
“…Computer-assisted kinematic analysis has been used to characterize gait patterns in animals with musculoskeletal pathology. [1][2][3][4][5][6][7] Although there are different kinematic analysis systems available, video-based motion analysis using superficial skin markers is the most commonly reported method of kinematic data acquisition of the hindlimb in dogs. [1][2][3][4][5][6]8,9 DeCamp and colleagues described a two-dimensional kinematic model of the hindlimb in dogs, most commonly used to describe sagittal plane motion.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although there are different kinematic analysis systems available, video-based motion analysis using superficial skin markers is the most commonly reported method of kinematic data acquisition of the hindlimb in dogs. [1][2][3][4][5][6]8,9 DeCamp and colleagues described a two-dimensional kinematic model of the hindlimb in dogs, most commonly used to describe sagittal plane motion. This model has been widely used to date [1][2][3][4][5][6]10,11 and uses superficial skin markers placed over anatomical landmarks for easy identification and repeatable placement.…”
Section: Introductionmentioning
confidence: 99%
“…This angle is measured in sagittal plane, based on the mechanical axes of the femur and tibia. The proximal landmark of the femoral axis (FA) is the greater trochanter, while the distal landmarks have changed from the lateral epicondyle, to the most distal point of lateral epicondyle, femorotibial joint centre or between the lateral epicondyle of the femur and fibular head (DeCamp et al., ; Hottinger et al., ; Sanchez‐Bustinduy et al., ; Torres et al., ; Agostinho et al., ; Bush et al., ; Nagano et al., ; Ragetly et al., ; Miqueleto et al., ; Robbins et al., ; Silvernail et al., ). However, all these approaches have ignored the anterior bow of the femur, where the compressive and ground reaction forces traverse from proximal to distal, or vice versa.…”
Section: Introductionmentioning
confidence: 99%